Path analysis of factors influencing length of stay and hospitalisation expenses for oral cancer patients in tertiary hospitals in southeastern China: a cross-sectional study - Jing Wang; Chen Chen; Xiaoying Hu; Yi Fan; Yaping Wang; Yu Qiu; Qiujiao Yang; Mingming Xu; Yanfeng Weng; Yanni Li; Lisong Lin; Fa Chen; et al. (BMJ Open)
Aims To investigate the associations between influencing factors with length of stay (LOS) and hospitalisation expenses in oral cancer (OC) patients, and to explore the potential pathways through which these factors influence hospitalisation expenses using path analysis.Design Cross-sectional.Setting A comprehensive tertiary hospital in southeastern China.Participants A total of 810 patients with histologically confirmed primary OC admitted to the First Affiliated Hospital of Fujian Medical University, Fujian Province, between 2015 and 2020.Main outcome measures LOS and hospitalisation expenses for OC patients.Results The median hospitalisation expenses and LOS for OC patients in southeastern China were substantial, amounting to $6330 and 29 days, respectively. Treatment and surgery fees constituted the largest proportion of total expenses (28.59%), followed by inspection and laboratory test fees (20.63%), comprehensive medical service fees (19.27%), drug fees (18.09%) and medical consumables fees (11.69%). LOS was significantly associated with tumour site, surgery and chemotherapy. Factors such as longer LOS, poor oral hygiene, advanced tumour stage (II–IV), larger tumour size (>2 cm3), surgery and bilateral neck dissection were strongly linked to higher hospitalisation expenses. Path analysis revealed that neck dissection had the highest total effect on hospitalisation expenses (β=0.307), while surgery exerted an indirect effect on expenses via LOS (β=0.021).Conclusion This study highlights the significant economic burden imposed by OC on patients and healthcare systems. While prevention and early diagnosis remain critical, our findings underscore several modifiable factors, including improving oral hygiene and optimising surgical protocols, such as chemotherapy and lymph node dissection, that present opportunities to reduce costs and enhance cost-effectiveness. These insights provide actionable targets for mitigating financial burdens and improving patient outcomes.